Ելիզավետպոլի և Շամխորի իրադարձությունները Անդրկովկասում իշխանության հիմնահարցի համատեքստում (1917 թ. նոյեմբեր–1918թ. փետրվար) - Վահան Մելիքյան (ՀՀ ԳԱԱ հրատ.)
С ноября 1917 г. покидавшие Кавказский фронт русские части столкнулись с организованным сопротивлением с одной стороны грузино-татарского руководящего большинства Закавказского комиссариата и краевого антибольшевистского центра совета солдатских и рабочих депутатов, а с другой–с антироссийскими акциями, которыми руководил возглавляемый партией «Мусават» Мусульманский национальный комитет. Since November 1917 the Russian forces that had been leaving the Caucasian front met consistent and purposeful barriers: on one hand the operations of Transcaucasian Commissariat of Georgian-Tatar head majority, Center of anti-Bolshevik land Council of military and working Deputies, on the other hand anti-Russian operations of Muslim National Committee that was administered by “Musavat” party.
Keywords: History; Political Science; Modern History; D History; J Political Science